Hyperspectral data processing chain development perspectives for vegetation studies - Bakos, Károly (TÁJÖKOLÓGIAI LAPOK, 2008)
In this paper the possibilities of hyperspectral data processing is investigated regarding to the application of these images in natural and ecological applications. A short overview is given of the available methods for interpretation purposes and special attention is paid on how the unique properties of hyperspectral data are affecting the choice from available methods for data processing. A broad identification of possible processing chain is discussed with the aim of developing more modular and application driven way of processing of the large data volumes. Automatic or semi-automatic procedures are proposed and key steps are to be identified that could lead to high quality mapping products by means of digital signal processing. Some experimental results are published and the broad methodology is presented that is aimed to use for identify data processing chain for vegetation mapping purposes. This work is to be continued with testing the performance at different stages of interpretation while different techniques are used. Furthermore over the HYPER-I-NET research network a document is to be supplied with the collection of results and application specific suggestions regarding to hyperspectral data processing for vegetation monitoring purposes.